2019
DOI: 10.4049/jimmunol.1801569
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine Synthesis from l-Citrulline in Myeloid Cells Drives Host Defense against Mycobacteria In Vivo

Abstract: Immunonutrition as a therapeutic approach is rapidly gaining interest in the fight against infection. Targeting l-arginine metabolism is intriguing, considering this amino acid is the substrate for antimicrobial NO production by macrophages. The importance of l-arginine during infection is supported by the finding that inhibiting its synthesis from its precursor l-citrulline blunts host defense. During the first few weeks following pulmonary mycobacterial infection, we found a drastic increase in l-citrulline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 54 publications
(73 reference statements)
1
25
0
Order By: Relevance
“…The only consistently decreased metabolite of these urea cycle intermediates in all three species is citrulline. Interestingly, previous studies have shown that arginine depletion as a result of arginase activity can be replenished from citrulline in macrophages and T-cells and thereby plays a role in immune defense 37,38 . Although in zebrafish larvae, the T-cells are not yet developed 39 , functional macrophages that can express arginase are present 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The only consistently decreased metabolite of these urea cycle intermediates in all three species is citrulline. Interestingly, previous studies have shown that arginine depletion as a result of arginase activity can be replenished from citrulline in macrophages and T-cells and thereby plays a role in immune defense 37,38 . Although in zebrafish larvae, the T-cells are not yet developed 39 , functional macrophages that can express arginase are present 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of TB disease, arginase 1 (Arg1) expression in myeloid cells from TB granulomas has been demonstrated to exacerbate disease through substrate competition with NOS 28,29 . Citrulline, however, was shown to fuel antimycobacterial mechanisms of murine macrophages 30,31 and T-cells 32 as an alternative source of intracellular arginine, implying that decreased citrulline levels could be detrimental for TB patients. Although the importance of arginase and NO production for the antimycobacterial response in humans remains controversial, ARG1 was found to be expressed in granulomatous tissue of TB patients 33,34 and could therefore play a role in TB pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…As such, studies determining the contribution not only of L-ARG utilization, but also of L-ARG synthesis during NAFLD are warranted. The necessity of L-ARG synthesis within macrophages has recently been described during infection, suggesting extracellular L-ARG is not available in sufficient concentrations to drive effective macrophage function (135,146,147). Accounting for the considerable influx of inflammatory macrophages in NAFLD, future studies aimed at addressing macrophage-specific modulation of L-ARG metabolism with existing molecular tools (e.g., Arg1 flox , Asl flox , Nos2-deficient) (148-150) will be necessary to dissect how various macrophage populations manipulate the liver microenvironment and NAFLD progression.…”
Section: Argininementioning
confidence: 99%